The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1016/j.ijid.2021.12.309
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 memory B and T cell profiles in mild COVID‐19 convalescent patients

Abstract: Objectives . Antiviral adaptive immunity involves memory B-(MBC) and T-cells (MTC), however their dynamics in SARS-CoV-2 convalescents warrant further investigation. Methods . In the cross-sectional and longitudinal study, we evaluated blood-derived MBC- and MTC-responses in 68 anti-spike IgG-positive mild-COVID-19 convalescents at visit 1 between 1-7 months (median 4.1 months) after disease onset. SARS-CoV-2 anti-spike IgG was performed by ELISA, MBC by SARS-COV-2 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…et al ( 226 ) detected memory T cells, which secrete IFN-γ and are able to clonally expand following SARS-CoV-2-antigen re-exposure, at least three months after disease onset. Further investigations have detected maintained SARS-CoV-2-specific memory T cell responses in COVID-19 convalescent patients at least 7-12 months after infection ( 217 , 221 , 227 ) and this has been found to be true regardless of disease severity ( 227 ). Considering immune memory at the tissue level, SARS-CoV-2-specific lung resident memory T cell can be detected at least 10 months following infection ( 228 ).…”
Section: Immune Memorymentioning
confidence: 95%
See 2 more Smart Citations
“…et al ( 226 ) detected memory T cells, which secrete IFN-γ and are able to clonally expand following SARS-CoV-2-antigen re-exposure, at least three months after disease onset. Further investigations have detected maintained SARS-CoV-2-specific memory T cell responses in COVID-19 convalescent patients at least 7-12 months after infection ( 217 , 221 , 227 ) and this has been found to be true regardless of disease severity ( 227 ). Considering immune memory at the tissue level, SARS-CoV-2-specific lung resident memory T cell can be detected at least 10 months following infection ( 228 ).…”
Section: Immune Memorymentioning
confidence: 95%
“…et al (245) defined most SARS-CoV-2 CD4+ T cells as displaying a central memory profile. Furthermore, Gurevich M. et al (221) reported the presence of IL-2-secreting and IFN-g+IL-2-secreting SARS-CoV-2-specific central memory T cells that might be long-lasting memory phenotypes in accordance with previous studies (246). There are two different subsets of CCR7+ stem cell-like progenitors: CCR7+PD-1−TIGIT− cells are observed to display stem cell-like features, whereas CCR7+PD-1+TIGIT+ cells seem to exhibit exhausted traits (192,247).…”
Section: Immune Memory Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…In mild COVID-19 convalescents, the peak memory B cell response was detected at 3 months after symptom onset and persisted up to 7 months after infection. Significant memory T cell levels were detected 1 month after disease onset and persisted even when specific humoral immunity declined [ 79 ]. The level of immune responses at 1 year post-COVID-19, mainly the phagocytic capacity and memory B cell responses, depended on the severity of the prior COVID-19 [ 80 ].…”
Section: Immune Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…IgM peaks on day 11-13 then decrease after 3 weeks besides IgG will be observed entirely on day 17-19 ( 52 ). The increase in IgG is followed by the formation of memory B cells for up to 3 months in length ( 53 ). Nevertheless, some patients with mild or asymptomatic symptoms were not found to be any seroconversion of these antibodies ( 54 ).…”
Section: Specific Immunity Against Sars-cov-2mentioning
confidence: 99%